Improved Adsorption Capacity of Nannochloropsis sp. through Modification with Cetyltrimethylammonium Bromide on the Removal of Methyl Orange in Solution. (7th October 2021) - Buhani,; Suharso,; Miftahza, Nurul; Permatasari, Desy; Sumadi,
Abstract : In this research, biomass modification of Nannochloropsis sp. with surfactant cetyltrimethylammonium bromide (CTAB) through a cation exchange reaction to produce adsorbent Nannochloropsis sp.-cetyltrimethylammonium bromide (AlgN-CTAB) has been carried out. Biomass modification of Nannochloropsis sp. by CTAB has been successfully carried out through confirmation from the analysis data produced by Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM-EDX). AlgN-CTAB adsorbent has been tested for its adsorption ability against anionic dye of methyl orange (MO) in solution by way of a sequence of experiments by the batch method. The optimum conditions for MO removal from the solution occurred at an adsorbent quantity of 0.1 g, pH of 5, and an interaction time of 60 min. MO adsorption kinetic data by AlgN and AlgN-CTAB tended to take the kinetic model of pseudo-second-order (PSO) with PSO rate constant (k 2 ) values of 0.56 and 2.17 g mg -1  min -1, serially. The MO adsorption isotherm pattern by AlgN tends to take the Freundlich adsorption isotherm, whereas in AlgN-CTAB it follows the Langmuir and Dubinin-Radushkevich adsorption isotherms. The results of the adsorption-desorption of MO by AlgN-CTAB with 4 repetition cycles resulted in % removal of MO > 80 % . The AlgN-CTAB adsorbent can be used repeatedly and is very effective in absorbing MO in water.